2022
DOI: 10.1158/2326-6066.cir-22-0362
|View full text |Cite
|
Sign up to set email alerts
|

Checkpoint Blockade–Induced Dermatitis and Colitis Are Dominated by Tissue-Resident Memory T Cells and Th1/Tc1 Cytokines

Abstract: Immune checkpoint blockade is therapeutically successful for many patients across multiple cancer types. However, immune-related adverse events (irAE) frequently occur and can sometimes be life-threatening. It is critical to understand the immunologic mechanisms of irAEs with the goal of finding novel treatment targets. Herein, we report our analysis of tissues from patients with irAE dermatitis using multiparameter immunofluorescence (IF), spatial transcriptomics, and RNA in situ hybridization (RISH). Skin ps… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 35 publications
(31 reference statements)
2
38
0
Order By: Relevance
“…As ICI-colitis appears dominantly Th1/Tc1-mediated disease, 14,15,17,43 Jak inhibition could be another treatment strategy in ICI-colitis. 44 Its safety from a tumor response perspective is presently not well established, however.…”
Section: Discussionmentioning
confidence: 99%
“…As ICI-colitis appears dominantly Th1/Tc1-mediated disease, 14,15,17,43 Jak inhibition could be another treatment strategy in ICI-colitis. 44 Its safety from a tumor response perspective is presently not well established, however.…”
Section: Discussionmentioning
confidence: 99%
“…In our recent publication we reported that T RM cells dominated in the inflammatory reactions associated with irAE-dermatitis and -colitis following checkpoint blockade immunotherapy. Biopsies showed and expansion of CD4+ and CD8+ T RM cells in percentage and numbers as assessed by multi-spectral immune fluorescence staining 5 . Spatial transcriptomics and confirmatory RNAscope were utilized to examine the transcriptional signatures of these expanded T RM cells.…”
Section: T Rm Cells and Immune Related Adverse Eventsmentioning
confidence: 99%
“…29 Spatial transcriptomic data have shown a higher expression of inhibitory receptors in dermatitis cases, as well as a portion of tissue-resident memory T cells aggregated to the inflamed part of the skin. 29…”
Section: Skin Cancermentioning
confidence: 99%